Laser response type high-entropy alloy-based initiating explosive material and preparation method thereof
By uniformly combining high-entropy alloy nanoparticles with high-energy compounds at the molecular level, and optimizing the material interface and band structure, a laser-responsive high-entropy alloy-based pyrotechnic agent was prepared. This solved the problems of low photothermal conversion efficiency and high threshold of existing agents, and achieved stable initiation under low laser energy triggering, thus improving the reliability and output energy of laser ignition.
Patent Information
- Application Number
- CN202511034974.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-25
- Publication Date
- 2025-10-31
AI Technical Summary
Current laser pyrotechnic agents have high response thresholds, low output energy, poor spectral compatibility, and insufficient response reliability, making it difficult to meet the actual usage requirements of laser-triggered pyrotechnics.
Laser-responsive high-entropy alloy-based pyrotechnic agents were prepared by using molecular-level homogeneous composites of high-entropy alloy nanoparticles and high-energy compounds, optimizing the material interface and band structure, and utilizing broadband plasmon resonance and efficient interband transition mechanisms.
It significantly enhances photothermal conversion efficiency, reduces the laser ignition threshold, enables stable initiation of secondary charges under low laser energy triggering, and provides a highly reliable ignition solution.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of energetic materials technology, and in particular to laser-responsive high-entropy alloy-based pyrotechnic agents and their preparation methods. Background Technology
[0002] Laser ignition, with its excellent resistance to electromagnetic interference and inherent safety, has significant application value in weaponry, aerospace, and engineering blasting. Its core ignition mechanisms can be divided into two categories: photothermal effect – energetic materials absorb photon energy and rapidly convert it into heat energy to initiate ignition; and direct laser dissociation – photons of specific frequencies cause molecular dissociation, generating highly reactive fragment molecules that trigger chain reactions. Although direct dissociation can achieve efficient energy transfer, it strictly depends on the precise matching of laser wavelength and material photoactivation energy. In practical applications, the vast majority of ignition processes are still dominated by the photothermal effect. Currently, existing laser pyrotechnics suffer from inherent defects such as high response threshold, low output energy, poor spectral compatibility, and insufficient response reliability. The fundamental reason lies in the limited plasma resonance bandwidth and untunable electronic bandgap characteristics of traditional materials, resulting in low energy utilization across the wide spectrum, especially in the near-infrared band, making it difficult to meet the practical needs of laser-triggered pyrotechnics. Summary of the Invention
[0003] Based on the current state of technology, the purpose of this invention is to provide laser-responsive high-entropy alloy-based pyrotechnic agents and their preparation methods to solve the problems of high laser ignition response threshold and low output energy.
[0004] The present invention solves the above-mentioned technical problems through the following technical means:
[0005] In a first aspect, embodiments of this application provide a method for preparing a laser-responsive high-entropy alloy-based pyrotechnic agent, comprising the following steps:
[0006] Weigh out the metal salt of acetylacetone, the surfactant and the reducing agent separately, and add them together to an organic solvent. Stir and mix well to obtain the precursor solution.
[0007] The precursor solution was heated to 180–220 °C and stirred for 2.5–3.5 hours. After the reaction was complete, it was cooled to room temperature, and the solid product was washed by centrifugation and dried to obtain high-entropy alloy nanoparticles.
[0008] High-entropy alloy nanoparticles and high-energy compounds were weighed separately and dispersed together in a mixed solvent. A dispersant was added, and the mixture was ultrasonically treated to form a uniform suspension. The suspension was then placed in a liquid nitrogen bath for freezing and subsequently dried in a freeze dryer to obtain a high-entropy alloy-based pyrotechnic agent.
[0009] In conjunction with the first aspect, in some embodiments, the acetylacetone metal salt is selected from at least five of the following: aluminum acetylacetone, calcium acetylacetone, chromium acetylacetone, iron acetylacetone, manganese acetylacetone, cobalt acetylacetone, nickel acetylacetone, copper acetylacetone, zinc acetylacetone, strontium acetylacetone, cadmium acetylacetone, and barium acetylacetone.
[0010] In conjunction with the first aspect, in some embodiments, the amount of the surfactant used is 0.4 to 0.8 times the mass of the acetylacetone metal salt.
[0011] In conjunction with the first aspect, in some embodiments, the mass ratio of the surfactant to the reducing agent is 1:1.
[0012] In conjunction with the first aspect, in some embodiments, the surfactant is hexadecyltrimethylammonium bromide or 1,2-hexadecanediol, and the reducing agent is glucose.
[0013] In conjunction with the first aspect, in some embodiments, the stirring and mixing is performed at 50–75°C for 25–40 minutes.
[0014] In conjunction with the first aspect, in some embodiments, the mass ratio of the high-entropy alloy nanoparticles to the high-energy compound is 1:(1.5 to 3).
[0015] In conjunction with the first aspect, in some embodiments, the high-energy compound is lead stearate or copper hexa(4-amino-3,5-dinitropyrazole) (Cu5(C3N5O4H2)6, abbreviated as Cu5), and the dispersant is hydroxypropyl cellulose.
[0016] In conjunction with the first aspect, in some embodiments, the mixed solvent is obtained by mixing tert-butanol and water at a volume ratio of 4:1.
[0017] Secondly, embodiments of this application also provide a laser-responsive high-entropy alloy-based pyrotechnic agent, which is prepared using the preparation method described in the first aspect above.
[0018] This invention relates to a laser-responsive high-entropy alloy-based pyrotechnic agent and its preparation method. High-entropy alloys (HEAs) are stable solid solutions formed through the synergistic effect of five or more metallic elements with equal atomic ratios, under the combined influence of the "high-entropy effect," "lattice distortion effect," "hysteresis diffusion effect," and "cocktail effect," endowing the material with unique properties surpassing those of traditional alloys. This invention utilizes the wide-spectrum plasmon resonance and efficient interband transition mechanism generated by laser excitation in HEAs to significantly enhance photothermal conversion efficiency and lower the laser triggering energy barrier of high-energy compounds (such as lead stearate or hexa(4-amino-3,5-dinitropyrazole)copper).
[0019] The laser-responsive high-entropy alloy-based pyrotechnic agent and its preparation method of the present invention uniformly load HEAs nanoparticles with broad-spectrum photothermal activity onto the surface of a thermosensitive energetic compound. By optimizing the material interface and band structure, stable initiation of secondary charges such as CL-20 under low laser energy triggering is achieved.
[0020] This invention relates to a laser-responsive high-entropy alloy-based pyrotechnic agent and its preparation method. High-entropy alloy nanoparticles with a broad-spectrum plasmon resonance effect are used as the laser energy conversion medium. A freeze-drying method is combined to achieve molecular-level homogeneous composite formation with high-energy compounds. The resulting laser-responsive high-entropy alloy-based pyrotechnic agent exhibits a broad-spectrum (440-1064 nm) plasmon resonance effect. Its molecular-level homogeneous composite system improves photothermal conversion efficiency. This technology reduces the laser ignition threshold to 10 mJ, enabling successful detonation of the secondary explosive CL-20 under laser irradiation. This invention solves the core problems of low photothermal conversion efficiency, high laser ignition threshold, and low output energy in traditional pyrotechnic agents, providing a highly reliable ignition solution for advanced weapon systems. Attached Figure Description
[0021] Figure 1 This is a schematic diagram of the laser-initiated detonation device and its charge.
[0022] Figure 2 These are the PXRD images of Examples 1-2;
[0023] Figure 3 These are TEM images, aberration-corrected electron microscopy images, and EDS-Mapping images of Examples 1-2;
[0024] Figure 4 These are XPS images of Examples 1-2;
[0025] Figure 5 This is a photothermal conversion diagram for Examples 1-2;
[0026] Figure 6 This is a diagram of a laser detonation device for a high-entropy alloy-based laser pyrotechnic agent.
[0027] Figure 7 This is a diagram of an explosion test. Detailed Implementation
[0028] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0029] In the embodiments of this application, the terms "exemplary" or "for example" are used to indicate that something is an example, illustration, or description. Any embodiment or design that is described as "exemplary" or "for example" in the embodiments of this application should not be construed as being more preferred or advantageous than other embodiments or designs. Specifically, the use of the terms "exemplary" or "for example" is intended to present the relevant concepts in a specific manner.
[0030] The preparation method of the laser-responsive high-entropy alloy-based pyrotechnic agent of this application includes the following steps:
[0031] Step (1): Weigh out the acetylacetone metal salt, surfactant, and reducing agent separately, and add them together to an organic solvent. Stir and mix thoroughly to obtain a precursor solution. In this step, the acetylacetone metal salt is selected from at least five of the following: aluminum acetylacetone, calcium acetylacetone, chromium acetylacetone, iron acetylacetone, manganese acetylacetone, cobalt acetylacetone, nickel acetylacetone, copper acetylacetone, zinc acetylacetone, strontium acetylacetone, cadmium acetylacetone, and barium acetylacetone, and the molar amount of each metal element in the acetylacetone metal salt is the same; the amount of surfactant is 0.4 to 0.8 times the mass of the acetylacetone metal salt, the mass ratio of surfactant to reducing agent is 1:1, the surfactant is hexadecyltrimethylammonium bromide or 1,2-hexadecanediol, the reducing agent is glucose, and the organic solvent is oleylamine; stirring and mixing are carried out at 50 to 75°C for 25 to 40 minutes to ensure that all raw materials are mixed evenly.
[0032] Step (2): The precursor solution is heated to 180-220°C and stirred for 2.5-3.5 hours to achieve simultaneous reduction of metal ions and growth of alloy cores. After the reaction is complete, the solution is cooled to room temperature and the solid product is dispersed in a 1:1 volume ratio of cyclohexane and ethanol mixed solution. The product is washed 5 times by centrifugation to remove unreacted impurities and surfactants. Finally, the precipitate is dried in a vacuum oven at 60°C for 12 hours to obtain high-entropy alloy nanoparticles.
[0033] Step (3): Weigh out the high-entropy alloy nanoparticles and high-energy compound according to a mass ratio of 1:(1.5-3), disperse them together in a mixed solvent, add a dispersant, and sonicate to form a uniform suspension. Place the suspension in a liquid nitrogen bath for freeze-drying to remove the mixed solvent, thus obtaining a high-entropy alloy-based pyrotechnic agent. In this step, the high-energy compound is lead stearate or Cu5, the dispersant is hydroxypropyl cellulose, and the mass of the dispersant is the same as that of the high-entropy alloy nanoparticles. The mixed solvent is tert-butanol and water mixed at a volume ratio of 4:1.
[0034] To better understand the above technical solutions, the following will provide a detailed explanation of the technical solutions in conjunction with the accompanying drawings and specific implementation methods.
[0035] Example 1
[0036] The laser-responsive high-entropy alloy-based pyrotechnic agent of this embodiment uses MnCoNiCuFe-HEAs in its preparation. The preparation method of the laser-responsive high-entropy alloy-based pyrotechnic agent of this embodiment is as follows:
[0037] Step (1): Accurately weigh equimolar amounts of manganese(II) acetylacetone [Mn(acac)2], cobalt(II) acetylacetone [Co(acac)2], nickel(II) acetylacetone [Ni(acac)2], copper(II) acetylacetone [Cu(acac)2], and iron(III) acetylacetone [Fe(acac)3] metal precursors, and add them sequentially to a dry reaction flask. The total mass of manganese(II) acetylacetone, cobalt(II) acetylacetone, nickel(II) acetylacetone, copper(II) acetylacetone, and iron(III) acetylacetone is 85 mg. Then add 50 mg of cetyltrimethylammonium bromide (CTAB) as a surfactant and 50 mg of glucose as a reducing agent. Then add 10 mL of oleylamine as a solvent. Stir continuously with magnetic force in a constant temperature oil bath at 65 °C for 30 min until all metal precursors are completely dissolved to form a homogeneous solution, and obtain the precursor solution.
[0038] Step (2): The precursor solution was then heated to 200°C and stirred with strong magnetic force for 3 hours to promote the co-reduction and alloying of metal ions. After the reaction was completed, the solution was naturally cooled to room temperature. The product was dispersed in a 1:1 mixture of cyclohexane and ethanol and centrifuged at 8000 rpm for 5 minutes. The product was washed 5 times by centrifugation to remove unreacted impurities and surfactants. Finally, the precipitate was dried in a vacuum oven at 60°C for 12 hours to obtain uniformly sized MnCoNiCuFe pentagonal high-entropy alloy nanoparticles, denoted as MnCoNiCuFe-HEAs.
[0039] Step (3): 100 mg of high-entropy alloy nanoparticles and 200 mg of Cu5 were co-dispersed in 60 mL of tert-butanol-water mixed solvent (V / V=4:1), and 100 mg of hydroxypropyl cellulose (HPC) was added as a dispersant. The mixture was ultrasonically treated to form a uniform suspension. The suspension was rapidly frozen in a liquid nitrogen bath for 10 min, then transferred to a -20 °C freezer for 6 h to form a porous network solid framework. The framework was then freeze-dried in a liquid nitrogen bath at -196 °C for 24 h to remove the tert-butanol solvent, thus obtaining a high-entropy alloy-based pyrotechnic agent, denoted as MnCoNiCuFe-HEAs@M1.
[0040] Example 2
[0041] The laser-responsive high-entropy alloy-based pyrotechnic agent of this embodiment uses FeCoNiCuCd-HEAs in its preparation. The preparation method of the laser-responsive high-entropy alloy-based pyrotechnic agent of this embodiment is as follows:
[0042] Step (1): Accurately weigh equimolar amounts of iron(III) acetylacetone [Fe(acac)3], cobalt(II) acetylacetone [Co(acac)2], nickel(II) acetylacetone [Ni(acac)2], copper(II) acetylacetone [Cu(acac)2], and cadmium(II) acetylacetone [Cd(acac)2] as metal precursors, and add them sequentially to a dry reaction flask. The total mass of iron(III) acetylacetone, cobalt(II) acetylacetone, nickel(II) acetylacetone, copper(II) acetylacetone, and cadmium(II) acetylacetone is 85 mg. Then add 50 mg of cetyltrimethylammonium bromide (CTAB) as a surfactant and 50 mg of glucose as a reducing agent. Then add 10 mL of oleylamine as a high-boiling-point solvent. Stir magnetically in an oil bath at 65 °C for 40 minutes until the solution is uniformly dark brown, which is the precursor solution.
[0043] Step (2): The system was then heated to 200℃ at a heating rate of 3℃ / min, and the temperature was maintained while the system was continuously magnetically stirred for 3 hours. The co-reduction of metal ions and the growth of alloy crystal nuclei were achieved through the coordination of oleylamine and the synergistic reduction of glucose. After the reaction was completed, the system was naturally cooled to room temperature, and the product was transferred to a centrifuge tube. A cyclohexane-ethanol (1:1 v / v) mixture was added, and the system was centrifuged at 8000 rpm for 5 minutes. The system was washed 5 times to remove residual organic ligands and unreacted precursors. Finally, the gray-black precipitate obtained by centrifugation was placed in a vacuum drying oven and dried at 60℃ overnight to obtain FeCoNiCuCd pentagonal high-entropy alloy nanoparticles, denoted as FeCoNiCuCd-HEAs.
[0044] Step (3): 100 mg of high-entropy alloy nanoparticles and 200 mg of Cu5 were co-dispersed in 60 mL of tert-butanol-water mixed solvent (V / V=4:1), and 100 mg of hydroxypropyl cellulose (HPC) was added as a dispersant. The mixture was ultrasonically treated to form a uniform suspension. The suspension was rapidly frozen in a liquid nitrogen bath for 10 min, then transferred to a -20 °C freezer for 6 h to form a porous network solid framework. The framework was then freeze-dried in a liquid nitrogen bath at -196 °C for 24 h to remove the tert-butanol solvent, thus obtaining a high-entropy alloy-based pyrotechnic agent, denoted as FeCoNiCuCd-HEAs@M1.
[0045] Example 3
[0046] The laser-responsive high-entropy alloy-based pyrotechnic agent of this embodiment uses MnCoNiCuFe-HEAs in its preparation. The preparation method of the laser-responsive high-entropy alloy-based pyrotechnic agent of this embodiment is as follows:
[0047] Step (1): Accurately weigh equimolar amounts of manganese(II) acetylacetone [Mn(acac)2], cobalt(II) acetylacetone [Co(acac)2], nickel(II) acetylacetone [Ni(acac)2], copper(II) acetylacetone [Cu(acac)2], and iron(III) acetylacetone [Fe(acac)3] metal precursors, and add them sequentially to a dry reaction flask. The total mass of manganese(II) acetylacetone, cobalt(II) acetylacetone, nickel(II) acetylacetone, copper(II) acetylacetone, and iron(III) acetylacetone is 125 mg. Then add 50 mg of 1,2-hexadecanediol as a surfactant and 50 mg of glucose as a reducing agent, and then inject 10 mL of oleylamine as a solvent. Stir continuously with magnetic force in a constant temperature oil bath at 65 °C for 30 min until all metal precursors are completely dissolved to form a homogeneous solution, and obtain the precursor solution.
[0048] Step (2): The precursor solution was then heated to 180°C and stirred with strong magnetic force for 2.5 hours to promote the co-reduction and alloying of metal ions. After the reaction was completed, the solution was naturally cooled to room temperature. The product was dispersed in a 1:1 mixture of cyclohexane and ethanol and centrifuged at 8000 rpm for 5 minutes. The product was washed 5 times by centrifugation to remove unreacted impurities and surfactants. Finally, the precipitate was dried in a vacuum oven at 60°C for 12 hours to obtain uniformly sized MnCoNiCuFe pentagonal high-entropy alloy nanoparticles, denoted as MnCoNiCuFe-HEAs.
[0049] Step (3): 100 mg of high-entropy alloy nanoparticles and 150 mg of lead stearate were co-dispersed in 60 mL of tert-butanol-water mixed solvent (V / V=4:1), and 100 mg of hydroxypropyl cellulose (HPC) was added as a dispersant. The mixture was ultrasonically treated to form a uniform suspension. The suspension was rapidly frozen in a liquid nitrogen bath for 10 min, then transferred to a -20 °C freezer for 6 h to form a porous network solid framework. The framework was then freeze-dried in a liquid nitrogen bath at -196 °C for 24 h to remove the tert-butanol solvent, yielding a high-entropy alloy-based pyrotechnic agent, denoted as MnCoNiCuFe-HEAs@M2.
[0050] Example 4
[0051] The laser-responsive high-entropy alloy-based pyrotechnic agent of this embodiment uses MnCoNiCuFe-HEAs in its preparation. The preparation method of the laser-responsive high-entropy alloy-based pyrotechnic agent of this embodiment is as follows:
[0052] Step (1): Accurately weigh equimolar amounts of manganese(II) acetylacetone [Mn(acac)2], cobalt(II) acetylacetone [Co(acac)2], nickel(II) acetylacetone [Ni(acac)2], copper(II) acetylacetone [Cu(acac)2], and iron(III) acetylacetone [Fe(acac)3] metal precursors, and add them sequentially to a dry reaction flask. The total mass of manganese(II) acetylacetone, cobalt(II) acetylacetone, nickel(II) acetylacetone, copper(II) acetylacetone, and iron(III) acetylacetone is 62.5 mg. Then add 50 mg of cetyltrimethylammonium bromide (CTAB) as a surfactant and 50 mg of glucose as a reducing agent. Then add 10 mL of oleylamine as a solvent. Stir continuously with magnetic force in a constant temperature oil bath at 75 °C for 40 min until all metal precursors are completely dissolved to form a homogeneous solution, and obtain the precursor solution.
[0053] Step (2): The precursor solution was then heated to 220°C and kept under strong magnetic stirring for 3.5 hours to promote the co-reduction and alloying of metal ions. After the reaction was completed, the solution was naturally cooled to room temperature. The product was dispersed in a 1:1 mixture of cyclohexane and ethanol and centrifuged at 8000 rpm for 5 minutes. The product was washed 5 times by centrifugation to remove unreacted impurities and surfactants. Finally, the precipitate was dried in a vacuum oven at 60°C for 12 hours to obtain uniformly sized MnCoNiCuFe pentagonal high-entropy alloy nanoparticles, denoted as MnCoNiCuFe-HEAs.
[0054] Step (3): 100 mg of high-entropy alloy nanoparticles and 300 mg of Cu5 were co-dispersed in 60 mL of tert-butanol-water mixed solvent (V / V=4:1), and 100 mg of hydroxypropyl cellulose (HPC) was added as a dispersant. The mixture was ultrasonically treated to form a uniform suspension. The suspension was rapidly frozen in a liquid nitrogen bath for 10 min, then transferred to a -20 °C freezer for 6 h to form a porous network solid framework. The framework was then freeze-dried in a liquid nitrogen bath at -196 °C for 24 h to remove the tert-butanol solvent, yielding a high-entropy alloy-based pyrotechnic agent, denoted as MnCoNiCuFe-HEAs@M3.
[0055] Using MnCoNiCuFe-HEAs, FeCoNiCuCd-HEAs, MnCoNiCuFe-HEAs@M1, and FeCoNiCuCd-HEAs@M1 as samples, the phase composition, morphology, particle size, and metal valence state of these samples were analyzed by X-ray diffraction, transmission electron microscopy, and X-ray photoelectron spectroscopy, as detailed below:
[0056] Figure 2The images are PXRD patterns of Examples 1-2, where a represents MnCoNiCuFe-HEAs and b represents FeCoNiCuCd-HEAs. Figure 3 The images shown are TEM images, spherical aberration electron microscope images, and EDS-Mapping images of Examples 1-2, where a is a TEM image, spherical aberration electron microscope image, and EDS-Mapping image of MnCoNiCuFe-HEAs; b is a TEM image and EDS-Mapping image of FeCoNiCuCd-HEAs. Figure 4 The images are XPS spectra of Examples 1-2, where a is the full and fine spectra of MnCoNiCuFe-HEAs; and b is the full and fine spectra of FeCoNiCuCd-HEAs. Figure 5 The figures are the photothermal conversion diagrams for Examples 1-2, where a is the photothermal conversion efficiency diagram of MnCoNiCuFe-HEAs under laser irradiation with power of 100Mw, 200mW, 300mW and 400mW; b is the photothermal conversion efficiency diagram of FeCoNiCuCd-HEAs under laser irradiation with power of 100Mw, 200mW, 300mW and 400mW. Figure 6 The diagram shows a laser initiation device for a high-entropy alloy-based laser pyrotechnic agent, where a is the laser initiation test device and b is the charging device for the initiating explosive and secondary explosive. Figure 7 The diagrams are for the detonation test, where a is the detonation test diagram of MnCoNiCuFe-HEAs@M1; and b is the detonation test diagram of FeCoNiCuCd-HEAs@M1.
[0057] Figure 2 The data show that MnCoNiCuFe-HEAs and FeCoNiCuCd-HEAs exhibit three characteristic diffraction peaks near 2θ of 43.7°, 51.0°, and 74.9°, respectively, with peak positions corresponding to the (111), (200), and (220) crystal planes of the face-centered cubic (FCC) structure. Furthermore, the absence of diffraction peaks for other impurities in the PXRD pattern indicates that the five metal elements achieved atomic-level homogeneous miscibility during high-temperature reduction, forming a single-phase FCC solid solution structure. This demonstrates the successful synthesis of high-entropy alloys of MnCoNiCuFe-HEAs and FeCoNiCuCd-HEAs.
[0058] Figure 3Data from model a show that the MnCoNiCuFe-HEAs nanoparticles are tightly attached to the surface of carbon nanotubes, forming a good interfacial bond. The MnCoNiCuFe-HEAs nanoparticles exhibit highly uniform size, with each particle precisely controlled to approximately 6.5 nm. Finally, energy-dispersive X-ray spectroscopy (EDS) mapping images revealed the distribution of the five metallic elements within the high-entropy alloy nanoparticles. The EDS-mapping images clearly show that Fe, Mn, Co, Ni, and Cu are uniformly distributed within each individual high-entropy alloy nanoparticle. Figure 3 Analysis revealed that the FeCoNiCuCd-HEAs nanoparticles were uniformly dispersed on the carbon nanotubes, indicating that the high-entropy alloy nanoparticles successfully adhered to the carbon nanotube surface during preparation, forming a uniform composite structure. EDS-mapping spectra showed the uniform distribution of Fe, Co, Ni, Cu, and Cd elements in the HEAs-CNTs material, further demonstrating the excellent dispersion of the high-entropy alloy particles within the carbon nanotubes. This result further confirms the strong bond between the high-entropy alloy nanoparticles and carbon nanotubes, and the effective control of elemental distribution during composite material preparation.
[0059] Figure 4 Data from model a shows that characteristic peaks for C, N, O, Fe, Mn, Co, Ni, and Cu can be observed in the figure. XPS peak fitting results indicate that the metallic elements in the FeMnCoNiCu high-entropy alloy nanoparticles exist in low valence states, with Cu, Ni, and Co mainly existing in valence states of 0 and +2; Mn mainly existing in valence states of +2 and +3; and Fe mainly existing in valence states of 0, +2, and +3. Figure 4 In spectrum b, the signal peaks of the corresponding elements Fe, Co, Ni, Cu, Cd, C and O can be clearly observed. The valence states of these elements were further analyzed by high-resolution spectra. The 0 and +2 valence signal peaks of Cd, Fe, Ni and Co indicate that these elements may coexist in the composite material in the metallic and oxidized states, while the fine spectral signal peaks of Cu indicate that it mainly exists in the 0 or +1 valence state.
[0060] Photothermal conversion efficiency is a crucial prerequisite for achieving safe and reliable laser-initiated ignition, directly determining the threshold and response accuracy of converting input energy into effective thermal energy for detonation. Two materials, MnCoNiCuFe-HEAs and FeCoNiCuCd-HEAs, were irradiated with different powers at the same time interval using a 1064 nm laser. The results were obtained by... Figure 5Analysis shows that Figures a and b depict the temperature response curves of the two materials at different power levels (100 mW to 400 mW). All curves exhibit a typical three-stage characteristic: a rapid temperature rise within the first 10 seconds (dominated by light absorption), followed by a thermal conduction equilibrium stage, and finally reaching dynamic thermal equilibrium after 60 seconds. The figures show that, at the same power, the overall temperature rise of FeCoNiCuCd-HEAs is significantly higher than that of MnCoNiCuFe-HEAs by approximately 50°C, indicating that the material modification significantly enhances the photothermal conversion efficiency.
[0061] Laser-initiated detonation tests of MnCoNiCuFe-HEAs@M1 and FeCoNiCuCd-HEAs@M1 pyrotechnic agents were conducted using a self-built laser-initiated detonation test platform. Figure 6 It consists of a laser head, a fiber collimator, and a laser focusing lens. Figure 6 b consists of a secondary explosive charging device (the secondary explosive is CL-20), an initiating explosive charging device (containing MnCoNiCuFe-HEAs@M1 or FeCoNiCuCd-HEAs@M1), and a stainless steel cover plate.
[0062] pass Figure 7 Analysis shows that the five images of MnCoNiCuFe-HEAs@M1 clearly present the complete detonation process of the annular component filled with CL-20 explosive. Initially, the annular structure maintains its complete geometric shape; at the moment of detonation, a network of penetrating cracks appears on the surface of the component, ultimately leaving a dent on the aluminum plate. Figure 7 Analysis in b shows that FeCoNiCuCd-HEAs@M1 exhibits a relatively slow initiation response, but ultimately successfully initiates CL-20.
[0063] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the present invention, and all such modifications and substitutions should be covered within the scope of the claims of the present invention. Technical aspects, shapes, and structures not described in detail in this invention are all well-known technologies.
Claims
1. A method for preparing laser-responsive high-entropy alloy-based pyrotechnic agents, characterized in that, Includes the following steps: Weigh out the metal salt of acetylacetone, the surfactant and the reducing agent separately, and add them together to an organic solvent. Stir and mix well to obtain the precursor solution. The precursor solution was heated to 180–220 °C and stirred for 2.5–3.5 hours. After the reaction was complete, it was cooled to room temperature, and the solid product was washed by centrifugation and dried to obtain high-entropy alloy nanoparticles. High-entropy alloy nanoparticles and high-energy compounds were weighed separately and dispersed together in a mixed solvent. A dispersant was added, and the mixture was ultrasonically treated to form a uniform suspension. The suspension was then placed in a liquid nitrogen bath for freezing and subsequently dried in a freeze dryer to obtain a high-entropy alloy-based pyrotechnic agent.
2. The method for preparing the laser-responsive high-entropy alloy-based pyrotechnic agent according to claim 1, characterized in that, The acetylacetone metal salt is selected from at least five of the following: aluminum acetylacetone, calcium acetylacetone, chromium acetylacetone, iron acetylacetone, manganese acetylacetone, cobalt acetylacetone, nickel acetylacetone, copper acetylacetone, zinc acetylacetone, strontium acetylacetone, cadmium acetylacetone, and barium acetylacetone.
3. The method for preparing the laser-responsive high-entropy alloy-based pyrotechnic agent according to claim 1, characterized in that, The amount of the surfactant used is 0.4 to 0.8 times the mass of the acetylacetone metal salt.
4. The method for preparing the laser-responsive high-entropy alloy-based pyrotechnic agent according to claim 3, characterized in that, The mass ratio of the surfactant to the reducing agent is 1:
1.
5. The method for preparing the laser-responsive high-entropy alloy-based pyrotechnic agent according to claim 4, characterized in that, The surfactant is hexadecyltrimethylammonium bromide or 1,2-hexadecanediol, and the reducing agent is glucose.
6. The method for preparing the laser-responsive high-entropy alloy-based pyrotechnic agent according to claim 1, characterized in that, The mixing process involves stirring at 50–75°C for 25–40 minutes.
7. The method for preparing laser-responsive high-entropy alloy-based pyrotechnic agents according to claim 1, characterized in that, The mass ratio of the high-entropy alloy nanoparticles to the high-energy compound is 1:(1.5-3).
8. The method for preparing laser-responsive high-entropy alloy-based pyrotechnic agents according to claim 1, characterized in that, The high-energy compound is lead stearate or copper hexa(4-amino-3,5-dinitropyrazole), and the dispersant is hydroxypropyl cellulose.
9. The method for preparing the laser-responsive high-entropy alloy-based pyrotechnic agent according to claim 1, characterized in that, The mixed solvent is obtained by mixing tert-butanol and water at a volume ratio of 4:
1.
10. A laser-responsive high-entropy alloy-based pyrotechnic agent, characterized in that, It is prepared by the preparation method described in any one of claims 1-9.
Citation Information
Cited By
CrFeCoNiCuZnS six-element single-phase high-entropy sulfide photocatalytic material, preparation method thereof and application of CrFeCoNiCuZnS six-element single-phase high-entropy sulfide photocatalytic material in treatment of uranium-containing wastewater
CN121669275A